A Sixth-Grade Science Program. - Marino, Santo L. (Education Digest, 1959)
The article presents a reprint of the article "A Sixth-Grade Science Program," by Santo L. Marino, which appeared in the May 1959 issue of "The Massachusetts Teacher." It focuses on the special sixth-grade science program in Lexington, Massachusetts. The program focuses on a basic treatment of the physical sciences. Each student needs to acquire basic skills for a better interpretation of his environment. The units of study are specific problems, suggested experiments and demonstrations to aid in analyzing the problems, the concepts to be derived from the views of the problems in terms of discussions, and demonstrations and lists of reference that might be helpful to teachers and pupils in reaching additional conclusions regarding the basic scientific principles demonstrated by the lesson.